IMPACT DU TRANSFERT PROACTIF SUR L’APPRENTISSAGE MOTEUR (ILLUSTRATION EN SPORTS COLLECTIFS) - Benbernou Otmane; Bengenab Hadj; Benlakhel Mansour; Sebbane Mohammed; Belaid Mohamed (European Scientific Journal, ESJ, 2014)
This research theme is the impact of the proactive transfer of motor learning between handball and basketball; carry out of the first year of secondary school pupils (15-17 years) of high school IdrisSenouci of Mostaganem city (Algéria). This study aimed to show the existence of a reciprocal proactive transfer of motor learning in the subsequent practice between handball and basketball in the direction of basketball to handball. For this, I hypothesized that there is a reciprocal proactive transfer motor learning engine between handball and basketball in favour of the sense of basketball to handball. To realize this study, I selected a systematic sample of 184 pupils’ boys and girls representing 36.44% of the population retort on four groups, two experimental and two controls to compare their results. And in order to measure the impact of reciprocal proactive transfer of motor learning between handball and basketball, I have conceived an experience based on the experimental protocol of Schmidt (1975) which compares between the performances of an experimental group to those of the control group. Thus, and after analyzing the results of the experiment, it is proved that the proactive transfer of motor learning was embodied in the sense of basketball to handball depending on three statistical means that are the T Student's, the percentage of development, and the transfer index of Murdock.